Factors Influencing Subscription of IPO in Bangladesh - Rahman, Md. Tahidur; Hossain, Syed Zabid; Omar, Normah (International Journal of Economics, Management and Accounting, 2017)
Due to huge loss in the secondary market during the 2010-2011 stock market crash, small investors in Bangladesh involved themselves in IPO investment. This study, based on secondary data, depicts the IPO market in Bangladesh and also identifies the factors influencing IPO subscription times. The study documented 85% growth in the listed companies on the Dhaka Stock Exchange (DSE) through IPO during the last decade with an average number of 14.80 IPOs per year. Fixed price method was followed in most of the IPOs; whereas the book building method was followed in only 2.70% of IPOs. Earnings forecast, a very common phenomenon of IPO prospectus in developed countries, was hardly ever found in the IPO prospectus in Bangladesh. Multiple regression model indicates that market lot has significant positive, whereas EPS and offer price have insignificant negative influence on IPO subscription times. The current study has explored the existing scenario of IPOs in Bangladesh that will help regulators to undertake proper course of action in developing the stock market in Bangladesh. The study will help issuers assessing the potential subscription condition of an IPO candidate company and also contribute to the existing stock of knowledge.